Open and Closed Loop Control of a Transport Aircraft After Component Failure - Daşkiran, O.; Kavsaoğlu, Mehmet Şerif (American Institute of Aeronautics and Astronautics (AIAA), 2011)
Aircraft dynamics are severely affected by the damages and failures of components. If corrective commands are not supplied immediately, force and moment imbalances lead into catastrophic consequences. In this study, flight dynamics of two failure scenarios are analyzed. Necessary amounts of control deflections for post failure trim are calculated and this trim values are applied in an open loop manner. Using Linear Quadratic Regulator theory and the linearized aircraft model, a closed loop controller is designed. Nonlinear aircraft model further parametrized into State Dependent Coefficient form and State Dependent Riccati Equation method is utilized for nonlinear controller design. Flight simulations on the nonlinear aircraft model are performed for all control schemes and results are discussed

AIAA Guidance, Navigation and Control Conference 2011 -- 8 August 2011 through 11 August 2011 -- Portland, OR -- 97951

American Institute of Aeronautics and Astronautics (AIAA)